SOLVING THE INVERSE PROBLEM OF LATERAL LOGGING OF SALT-BEARING DEPOSITS - Kolosov A.L.; Slobodnik N.A. (My University, 2001)
Solution of the inverse problem of lateral logging is analysed for the case of identifying the interface between zones differing considerably in electrical conductivity, such as an interface between saline deposits dissolved in drilling mud and exhibiting low specific electrical resistance and undissolved saline deposits of high electrical resistivity.